HYPOTHYROIDISM AS MANIFESTATION OF POSTPARTUM THYROIDITIS - Putu Ayu Kevin Komala Dewi Mahayuna Putri; I Wayan Yuna Ariawan; I Wayan Eka Saputra (International Medical Journal Corp. Ltd, 2026)
Introduction:Postpartum thyroiditis (PPT) is a destructive autoimmune inflammatory disorder of the thyroid gland that occurs within one year after delivery in women without a prior history of thyroid disease. The condition is caused by an autoimmune process that induces thyroid follicular damage and thyroglobulin proteolysis. Clinically, PPT typically presents with a triphasic pattern, beginning with a transient thyrotoxic phase, followed by hypothyroidism, and ultimately progressing toward recovery to a euthyroid state. Case Illustration: A 37-year-old woman presented with a gradually enlarging anterior neck swelling without associated pain. The patient had no previous history of thyroid disease or autoimmune disorders. Five months before clinical assessment, she had delivered her third child. Thyroid function tests revealed hypothyroidism, while thyroid ultrasonography demonstrated findings consistent with thyroiditis. The patient was subsequently treated with levothyroxine and scheduled for monthly follow-up evaluations. Following treatment, thyroid hormone levels returned to within normal limits, and the neck swelling gradually decreased. Discussion:The hypothyroid phase of postpartum thyroiditis (PPT) may occur due to depletion of thyroglobulin stores and cessation of the proteolytic process, resulting in decreased serum T3 and T4 levels. Patients with symptomatic hypothyroidism, as well as asymptomatic individuals with TSH levels >10 mU/L, are recommended to receive levothyroxine therapy at a dose of 50–100 mcg daily accompanied by periodic thyroid function monitoring. Most patients recover completely and return to a euthyroid state within one year. However, persistent hypothyroidism may develop in up to 50% of patients despite initial clinical improvement. Conclusion: The diagnosis of postpartum thyroiditis remains challenging because its clinical manifestations are often subtle and nonspecific. Therefore, a multidisciplinary approach is essential to ensure continuity of thyroid disorder management from pregnancy through the postpartum period.